Evaluation of the impact of enhanced virtual forms and gamification on intervention identification in a pharmacist-led ambulatory care clinic - Courtney E. Gamston; Joshua C. Hollingsworth; Brent I. Fox; Sylvia Rogers, PhD; Mary Elizabeth O'Barr; Kimberly Braxton Lloyd (Elsevier, 2021)
Background: Adoption of healthcare technology in the ambulatory care setting is nearly universal. Clinical decision support system (CDSS)22 CDSS - clinical decision support system. technologies improve patient care through the identification of additional care opportunities. With the movement from paper-based to electronic clinical intake forms, the opportunity to improve identification of gaps in care utilizing CDSS in the ambulatory care setting exists. Objective: To evaluate the impact of CDSS-enhanced digital intake forms, with- and without aspects of gamification, on the identification of intervention opportunities in an ambulatory care pharmacy setting. Methods: Patients were invited to complete visit intake paperwork via virtual forms as part of a CDSS-enhanced mobile application designed to identify potential interventions based on patient age, sex, disease state(s), and user-provided information. Patients were randomized to receive optional patient-specific health questions 1) with or 2) without elements of gamification. Gamification elements included trivia questions, fun facts, and the chance to win a prize. A retrospective review was used to assess interventions identified for a random sample of patients seen within the same time frame who did not utilize the mobile application. Interventions were compared across groups utilizing ANOVA. t-tests were used for a subgroup analysis. Results: From January to May 2019, 353 potential interventions were identified for 220 study participants. 0.44 (±0.82), 1.8 (±2.0) and 2.1 (±1.8) interventions per participant were identified for the control, virtual forms, and virtual forms + gamification groups, respectively. Significant differences in intervention identification across groups were found using a one-way ANOVA (F = 17.46, p < .001). Post hoc analysis demonstrated a significant difference in interventions identified for those completing 50-100% (n = 32) and those completing less than 50% (n = 18; p < .001) of the optional health questions in the virtual forms + gamification group. Conclusions: Utilization of CDSS-enhanced clinical intake forms increased identification of potential interventions, though gamification did not significantly impact this identification.